Antihypertensive Drugs Therapy in Hypertension and Covid-19 Comorbidity - Emuesiri Goodies Moke; Endurance Efe Ahama; Pere-Ebi Yabrade Toloyai; Mamerhi Taniyohwo Enaohwo; Ekuerhare Basil; Emuesiri Kohworho Umukoro; Anthony Taghogho Eduviere; Ikuesirioghene Udumebraye; Choice Udufowe (Biology, Medicine, & Natural Product Chemistry, 2023)
The novel coronavirus (CoV) severe acute respiratory syndrome (SARS)-CoV-2 outbreak began at the end of 2019 in Wuhan, China, and has spread to over 200 countries. Many comorbidities have shown to be associated with the severity of the viral infection with hypertension being one of the highest rated comorbidities since loss of the ACE2 receptor due to SARS-Cov-2 infection can lead to increased blood pressure. The effects and clinical characteristics associated with the use of beta-blockers, angiotensin receptor blockers (ARB), and calcium-channel blockers (CCB) shows not to affect the outcome of covid-19, except in angiotensin converting enzyme inhibitor (ACEI) which may have negative outcomes on covid-19 infected patients. Many comorbidities have shown to be associated with the severity of the viral infection.